Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1589/jpts.27.2977
|View full text |Cite
|
Sign up to set email alerts
|

Walking ability after stroke in patients from Argentina: predictive values of two tests in subjects with subacute hemiplegia

Abstract: [Purpose] This study aimed to determine the predictive values of the trunk control test (TCT) and functional ambulation category (FAC) for independent walking up to 6 months post stroke. [Subjects] Twenty-seven subjects with hemiplegia secondary to a unilateral hemisphere stroke were included. [Methods] The protocol was started at 45 days post stroke, with the TCT and FAC as walking predictors. At 90, 120, and 180 days post stroke, the subjects’ independent walking ability was assessed by using the Wald test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…The ability to walk is largely controlled by the central nervous system (CNS) in which the brain is an integral part [ 1 3 ]. This control is however impaired in conditions that affect the brain such as stroke in which motor function of the lower limbs is impaired [ 4 , 5 ]. Thus, one of the most important goals in stroke rehabilitation is to help patients regain motor function of the lower limbs and consequently the ability to walk independently as much as possible in order to ensure the ability to carry out ADLs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to walk is largely controlled by the central nervous system (CNS) in which the brain is an integral part [ 1 3 ]. This control is however impaired in conditions that affect the brain such as stroke in which motor function of the lower limbs is impaired [ 4 , 5 ]. Thus, one of the most important goals in stroke rehabilitation is to help patients regain motor function of the lower limbs and consequently the ability to walk independently as much as possible in order to ensure the ability to carry out ADLs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke, with a high prevalence and long-term disabilities, is a major health problem in the world 1 , 2 ) , and it was reported that about two million people suffer from stroke each year 3 ) . Impairments including loss of strength, sensation, and coordination abilities, which result in walking difficulties, balance disorders, and limb function disturbance, occur in 70–80% of stroke patients 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is described as a neurologic disease that suddenly occurs due to the loss of brain function resulting from an abnormal decrease in the blood supply 1 ) . With its high occurrence rate, stroke is one of the major causes of death worldwide 2 ) .…”
Section: Introductionmentioning
confidence: 99%